1.116. Rozwiąż nierówności: a) 2(x – 1) – 3(x – 2) < 6 c) e) g) 1 8 (5,6x 6x-4)<=0,3x+4,5 (x - 5)/7 < (3x + 2)/21 (4 - x)/5 - (x + 2)/3 >= (2 – 8x)/15 b) 5 >= 2x + 1 >= – 5 d) 3 > – x >= – 7 f) h) – x + 6 <= 2x <= 3x + 1 5x - 6 <= - 3x + 2 <= x - 2 b) - 3(2x + 4) + 5(x - 2) >= – x + 5 d) – 1 2/3 * (x + 6) >= 1/6 * (x + 3) + 0, 5 (x + 2)/3 – (x + 4)/4 > (x + 1)/12 (x – 5)/2 – (3 – x)/6 <= (x + 4)/3 f) h)

1.116. Rozwiąż nierówności: a) 2(x – 1) – 3(x – 2) < 6 c) e) g) 1 8 (5,6x 6x-4)<=0,3x+4,5 (x – 5)/7 < (3x + 2)/21 (4 – x)/5 – (x + 2)/3 >= (2 – 8x)/15 b) 5 >= 2x + 1 >= – 5 d) 3 > – x >= – 7 f) h) – x + 6 <= 2x <= 3x + 1 5x – 6 <= – 3x + 2 <= x – 2 b) – 3(2x + 4) + 5(x – 2) >= – x + 5 d) – 1 2/3 * (x + 6) >= 1/6 * (x + 3) + 0, 5 (x + 2)/3 – (x + 4)/4 > (x + 1)/12 (x – 5)/2 – (3 – x)/6 <= (x + 4)/3 f) h)